2010
DOI: 10.1136/bmj.c2096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antibiotic prescribing in primary care on antimicrobial resistance in individual patients: systematic review and meta-analysis

Abstract: Objective To systematically review the literature and, where appropriate, meta-analyse studies investigating subsequent antibiotic resistance in individuals prescribed antibiotics in primary care. Design Systematic review with meta-analysis.Data sources Observational and experimental studies identified through Medline, Embase, and Cochrane searches.Review methods Electronic searches using MeSH terms and text words identified 4373 papers. Two independent reviewers assessed quality of eligible studies and extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
1,240
2
50

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,653 publications
(1,320 citation statements)
references
References 38 publications
28
1,240
2
50
Order By: Relevance
“…This association has been described in several studies; e.g. a meta-analysis showing the effect of antibiotic prescribing in primary care on bacterial resistance [6] and a cross-national database study linking resistance levels observed with consumption of antimicrobial agents in European countries [7]. However, other studies have shown inconsistent results and the authors concluded that antimicrobial resistance is influenced by many factors, especially by linkages between resistance properties [8,9].…”
Section: Introductionmentioning
confidence: 83%
“…This association has been described in several studies; e.g. a meta-analysis showing the effect of antibiotic prescribing in primary care on bacterial resistance [6] and a cross-national database study linking resistance levels observed with consumption of antimicrobial agents in European countries [7]. However, other studies have shown inconsistent results and the authors concluded that antimicrobial resistance is influenced by many factors, especially by linkages between resistance properties [8,9].…”
Section: Introductionmentioning
confidence: 83%
“…It Is unlikely that all primary care clinicians follow optimal guidelines in their antibiotic prescribing – this is one of the causes of antibiotic resistance 3 . Yet evidence‐based guidelines are seen as an important means of changing over‐prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…Their over‐prescription may be contributing to antibiotic resistance 3 . This is recognised as a serious threat, putting recovery from serious infection in doubt, and beginning to risk many therapeutic and diagnostic interventions in tertiary care requiring secure antibiotic cover – something now labelled a global threat 4 , 5 …”
mentioning
confidence: 99%
“…16 Whilst ciprofloxacin, third-generation cephalosporins, gentamicin and carbapenems are less frequent first-line therapies for UTIs, 14 they are important for treating more severe infections, thus non-susceptibility trends should be monitored.…”
Section: While Large Declines In Infections Such As Methicillin-resismentioning
confidence: 99%